Cultural-Value-Based Bureaucratic Reform in North Halmahera Regency - Kadir, A. Gau (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2015)
Researches on bureaucratic reform based on cultural value (cultural approach) are rarely found. In fact, the combining use of structural and cultural approaches in government bureaucratic reform can be expected to encourage the achievement of bureaucratic reform objectives. This study chose the location in North Halmahera Regency, where the community still uphold the cultural values as represented in its cultural symbol of "Hibua Lamo." The research uses a qualitative method and the technique of content analysis. "Hibua Lamo" gives birth to various cultural values and social norms that are formally enacted, putting "Hibua Lamo" into a pattern of organization in society and government. The Regent of North Halmahera implemented a bureaucratic reform in his local governance based on the considerations of balance between "institutional power" according to legislation and social norms institutionalized in "Hibua Lamo". The combined consideration of balance between the legislation and the institutionalized social norms made the Regent of North Halmahera capable to implement the policies of bureaucratic reform in North Halmahera, thereby building an efficient, effective and well-performed bureaucracy as well as reducing poverty from 57.16% to 9.97%, increasing annual per capita income of about 30%, and encouraging economic growth in North Halmahera Regency approximately 6.04%.